Book review: Guide to the world’s top universities / Richard Holmes - Holmes, Richard (ACRULeT, Faculty of Education & UiTM Press, 2007)
Guide to the World’s Top Universities, John O’Leary, Nunzio Quacquarelli and Martin Ince. QS Quacquarelli Symonds Ltd.: London. 2006.